A Salt-Signaling Network Involving Ethylene, Extracellular ATP, Hydrogen Peroxide, and Calcium Mediates K(+)/Na(+) Homeostasis in Arabidopsis - Lang, Tao (Int J Mol Sci, 2020)
This work aimed at investigating the interactive effects of salt-signaling molecules, i.e., ethylene, extracellular ATP (eATP), H(2)O(2), and cytosolic Ca(2+) ([Ca(2+)](cyt)), on the regulation of K(+)/Na(+) homeostasis in Arabidopsis thaliana. The presence of eATP shortened Col-0 hypocotyl length under no-salt conditions. Moreover, eATP decreased relative electrolyte leakage and lengthened root length significantly in salt-treated Col-0 plants but had no obvious effects on the ethylene-insensitive mutants etr1-1 and ein3-1eil1-1. Steady-state ionic flux kinetics showed that exogenous 1-aminocyclopropane-1-carboxylic acid (ACC, an ethylene precursor) and eATP-Na(2) (an eATP donor) significantly increased Na(+) extrusion and suppressed K(+) loss during short-term NaCl treatment. Moreover, ACC remarkably raised the fluorescence intensity of salt-elicited H(2)O(2) and cytosolic Ca(2+). Our qPCR data revealed that during 12 h of NaCl stress, application of ACC increased the expression of AtSOS1 and AtAHA1, which encode the plasma membrane (PM) Na(+)/H(+) antiporters (SOS1) and H(+)-ATPase (H(+) pumps), respectively. In addition, eATP markedly increased the transcription of AtEIN3, AtEIL1, and AtETR1, and ACC treatment of Col-0 roots under NaCl stress conditions caused upregulation of AtRbohF and AtSOS2/3, which directly contribute to the H(2)O(2) and Ca(2+) signaling pathways, respectively. Briefly, ethylene was triggered by eATP, a novel upstream signaling component, which then activated and strengthened the H(2)O(2) and Ca(2+) signaling pathways to maintain K(+)/Na(+) homeostasis under salinity.